The Development of Science Process Skills and Content Knowledge with Inquiry Boxes in Early Childhood Education - Nika Golob; Vanja Ungar (Center for Educational Policy Studies Journal)
This paper aims to investigate the systematic use of an inquiry-based learning approach in science by using inquiry boxes for preschool children. We prepared four thematic inquiry boxes for the areas of magnetism and buoyancy, separation of substances, weighing objects, and the investigation of substances. The research sample consisted of twenty children aged four to five years. Ten children from the experimental group explored the material using the photo-type instructions on the instructional cards over a period of four weeks. Comparative test results for the control group children show that the experimental group children progressed both in content knowledge and in better-developed science process skills. We find that children develop autonomy in science process skills such as classifying, ordering, and weighing through prepared and guided inquiry with the help of the inquiry boxes. In doing so, children show increasing autonomy within each set of tasks that develop the chosen science process skill. In this manner, science practices with inquiry boxes allow children to build on science content knowledge. They can apply the skills they have learned through inquiry boxes to new knowledge instead of teaching science processes as isolated skills. This approach of individually guided inquiry by children using thematic inquiry boxes is therefore recommended as a proven didactic tool for developing science process skills and content knowledge.